(untitled) (Construction Economics and Building, 2022)
This study assessed the risks level associated with implementation of sustainable construction practices through a questionnaire survey distributed to 256 building professionals in Nigeria. It identified 47 risk factors with different likelihood of occurrence and magnitude of impacts. A quantitative risk analysis result based on mean value method and risk prioritisation number showed that the three top-ranked risk factors with highest likelihood of occurrence were unavailability of sustainable materials and equipment, more complex and unfamiliar construction techniques and processes, and high initial sustainable construction costs; whereas the three top-ranked risk factors with highest magnitude of impacts were high initial sustainable construction costs, poor and inefficient communication among project participants, and high cost of sustainable materials and equipment. The criticality index result identified 23 critical risk factors which mostly related to knowledge and awareness, cost, regulatory framework, building materials and socioeconomic issues. However, the Wilcoxon Signed-rank test result indicated that there is significant difference (z = -3.207, p<0.001) between the likelihood of occurrence and magnitude of impacts of the risks factors associated with implementation of sustainable construction practices in Nigeria of which the effect was moderate (r = 0.468). Furthermore, the study revealed that there is no significance difference in the risk level of the risk factors associated with implementation of sustainable construction practices based on the respondents’ roles (p>0.05). The study, therefore, recommended for training of construction practitioners in the multi-risk management approaches and increasing awareness through education on sustainable construction concept for building industry stakeholders. It further recommended for developing of new sustainable and affordable building materials through research institutes like Nigerian Building and Road Research Institute (NBRRI) with appropriate regulatory and policy frameworks for successful sustainable building projects.